Efficiency Evaluation of Primary and Secondary Education Sector Performance in East Java Using Data Envelopment Analysis - Bahalwan Apriyansyah; Syarifa Hanoum; Prahardika Prihananto; Siti Lailatul Mukaromah (Institut Teknologi Sepuluh Nopember, 2020)
Education has an important role in creating excellent human resources for the advancement of national development. However, in Indonesia, there are still gaps in equal access to education. This study aims to evaluate the performance efficiency of the education sector to provide recommendations of which considered inefficient by using the Data Envelopment Analysis (DEA) method. This study measures the technical efficiency of primary and secondary schools (junior and senior high school) in 38 regencies/cities in East Java Province for three academic years (2016-2019). The results showed that technical inefficiency still occurs in the implementation of education in East Java. In addition, peer groups and improvement targets were obtained for the inefficient regencies/cities. The indicators that most influence the efficiency value of the education sector in East Java are the Education Fund Allocation as the input variable and the School Continuing Rate as the output variable. The scale efficiency analysis shows that most of the education sector in East Java operates in decreasing returns to scale